Pendataan Tempat-Tempat Pariwisata di Kota Balikpapan Serta Perbatasan Wilayah Kutai Kartanegara di Samboja - Ulum Janah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
Tourism is one of the capital in increasing the income of a region. Through culture, the traditions of local people also have a stake in developing the tourism sector of an area. The potential in terms of culture, nature, and man-made become an attraction for visitors. Not just for refreshing, tourism potential can also add insight into both religion and philosophical values in it. This service is done by using the method of collecting data using and in-depth interviews through observation to find out directly through interviewing the speakers around the tourist attractions. Data inventoried both in terms of culture, nature, and artificial without heeding the values of philosophy or symbols contained in the culture in the place. The city of Balikpapan and the borders of the Kutai Kartanegara region, namely Amburawang and Samboja, also have several supporting places as tourist attractions. In addition to its still attractive nature, culture as a potential supporter can be found in several places in these areas such as religious tourism, culinary tourism, or in accordance with the economic system of the surrounding community. Thus, culture is one of the strong supporters of the increase in tourism in the area. Keywords: Tourism, Culture, Balikpapan, and Samboja